1988
DOI: 10.1177/153450848801300404
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Self-Recognition in Young Children with Handicaps

Abstract: Thirty pung childmn with handicaps were assessed using a series of five self-recognition mirm tasks developed by Bettentha1 and Fischer (1978a, 1978b). The task data were submitted to a Guttman Scalogram. Generalh the set o f items did form a mproducibh? scale, indicating these tasks are an a w p f i a t e measure of se#-mognitim in young children with handicaps. Howaec some general differences m nded between task performance by this sample and those reported by the authors for nonhandicapped p n g chddren, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Research on the development of selfrecognition in children with disabilities has focused on children with intellectual disabilities (especially children with Down syndrome) and children with autism using the same mark and object tests discussed earlier. Studies on children with intellectual disability have found that they develop self-recognition in the same sequence as children without disabilities and in a similar timeframe when mental age is considered instead of chronological age (Hill & Tomlin, 1981;Kelly et al, 1988;Mans, Cicchetti, & Sroufe, 1978). Hill and Tomlin noted improved self-recog-nition performance as early as in the second study session of four, suggesting the importance of experience with images to the development of selfrecognition in children with intellectual disabilities.…”
Section: Achievement Of Self-recognition By Children With Disabilitiesmentioning
confidence: 96%
See 1 more Smart Citation
“…Research on the development of selfrecognition in children with disabilities has focused on children with intellectual disabilities (especially children with Down syndrome) and children with autism using the same mark and object tests discussed earlier. Studies on children with intellectual disability have found that they develop self-recognition in the same sequence as children without disabilities and in a similar timeframe when mental age is considered instead of chronological age (Hill & Tomlin, 1981;Kelly et al, 1988;Mans, Cicchetti, & Sroufe, 1978). Hill and Tomlin noted improved self-recog-nition performance as early as in the second study session of four, suggesting the importance of experience with images to the development of selfrecognition in children with intellectual disabilities.…”
Section: Achievement Of Self-recognition By Children With Disabilitiesmentioning
confidence: 96%
“…Self-recognition is the recognition of one's own image as representing oneself. Self-recognition is an early form of social cognition (Kelly, Sexton, Burdg, & Haynes, 1988) and is essential to learning to think about oneself and one's actions (Gallup, 1979) and to expressing empathy (Lewis & Ramsay, 1997). Self-recognition is a measure of self-awareness (Lewis & Ramsay) and its achievement influences other areas of development (Berk, 2002).…”
Section: Importance Of Self-recognitionmentioning
confidence: 99%